Resveratrol (trans-3,4', 5-trihydroxystilbene) decreases lipid peroxidation level and protects antioxidant capacity in sera and erythrocytes of old female Wistar rats induced by the kidney carcinogen potassium bromate - Yilmaz, Oekkes; Keser, Serhat; Tuzcu, Mehmet; Cetintas, Buket (Elsevier, 2007)
Resveratrol is a natural polyphenolic compound and it is found in number of edible plants, especially grapes and peanuts, has been shown to have anti -inflammatory, anti-oxidant, anti-tumor and anti-platelet activities. The aim of the study was to examine the effects of resveratrol on the level of malondialdehyde (MDA), homocysteine, cholesterol, GSH, GSSG and lipophylic vitamins in serum and erythrocytes of old female Wistar rats induced by the kidney carcinogen potassium bromate (KBrO3). In the study, total 30-old female Wistar rats were used, and the rats were randomly divided into three groups. The first group was used as a control, the second group KBrO3 group, and third group R + KBrO3. Rats in KBrO3 and R + KBrO3 groups were injected intraperitoneally a single dose KBrO3 (80 mg/kg) in physiologic saline buffer. After 2 days, those in R + KBrO3 group were intraperitoneally injected with resveratrol (33 mg/kg) four times per week, and physiological saline was injected to control group rats. All the analysis was performed fully automatic with high performance liquid chromatography equipment. The results indicate that serum cholesterol level in the R + KBrO3 group was higher than the control group (p < 0.05), and level of the cholesterol in erythrocytes membranes was lower in the same group (p < 0.0 1). The MDA level in serum and erythrocytes of the R + KBrO3 were lower than the control and KBrO3 groups (p < 0.0 1). However, the NIDA level in erythrocytes of the KBr03 group was high compared to the control group (p < 0.05). Homocysteine and 8-tocopherol levels in serum of the R + KBr03 group were lower than the control group (p < 0.05, p < 0.001). alpha-Tocopherol level in serum and erythrocytes of the KBrO3 group was lower than the control group (p < 0.05), whereas its level was not found to differ between the control and R + KBrO3 groups. GSH and GSSG levels in the K13r03 group of erythrocytes were higher than control group (p < 0.05, p < 0.0 1), however the ratio GSH/GSSG in the same group was lower than control group. In conclusion, our results confirm that the lipid peroxidation formation in serum and erythrocytes of old female Wistar rats by induced the KBrO3 is prevented by the resveratrol. It was observed that the antioxidant capacity of erythrocytes was protected by resveratrol. (c) 2007 Elsevier B.V All rights reserved.
Keywords: resveratrol; serum; erythrocytes; KBrO3; lipid peroxidation; homocysteine; cholesterol; glutathione; lipophylic vitamins